A preliminary investigation of the chemical nature of wattle tannin - Corbett, John Henry (Rhodes University, Faculty of Science, Department of Chemistry, 1945)
From Introduction: Although the tannins of wattle bark extract are generally considered to be of the class known as condensed tannins, a review of the general chemical nature of the tannins is given for the sake of completeness. This constitutes Part I of the thesis. Part II describes the preliminary investigation of the chemical nature of black wattle extract.
Keywords: Uncatalogued